Desplazados de Haití: movilidad intrarregional sudamericana y las medidas compulsivas en Brasil y Chile - Joseane Mariéle Schuck Pinto; Rodrigo Ríos Álvarez (Ciências Sociais Unisinos)
This paper analyzes the compulsory measures adopted by Brazil and Chile in processes of expulsion of migrants. The particular case of Haitian migration is studied, and what its implications have been at the judicial level, through a case study highlighting what have been the criteria and standards applied by the immigration authorities of both countries. In relation to the procedure to be adopted, it is observed that through qualitative research it will be possible to account for the different representations on the subject under study, without neglecting the quantitative method, as it will contribute to the evaluation and categorization of contained data in government information databases, such as data from the Ministry of Justice and Public Security of Brazil, the National Institute of Statistics and the Judiciary of Chile, and the Institute of Public Policies and Human Rights of Mercosur, with the elaboration of a diagnosis of the displacement of Haitians in South American countries, with special emphasis on the migratory realities of Haitians in Brazil and Chile. In the same way, the research includes the analysis of decisions adopted by the Superior Courts of Justice of Chile and Brazil, as well as the documentary and bibliographic survey, especially articles from specialized international magazines on the subject. In addition, the existing laws and public policies in Chile and Brazil, the conventions, protocols and other international instruments that help to better understand the reality studied will be consulted.